User experience study on mobile numerical application for children with mental disabilities - Aziz, N.S.A. (Institute of Electrical and Electronics Engineers Inc., 2014)
Mobile technology has expanded the use of information technology; it is now more than just a communication device. The use of mobile technology has also become more imperative to the education industry. Studies show that the use of mobile technology not only can aid the teaching and learning for the mainstream classrooms, but also can assist the teaching and learning of the mentally disabled students. The children with Down syndrome (DS) have special needs in their teaching and learning environments. Mobile learning environment can assists the DS children to be more focus during their learning activities. This paper presents about the user experience study of a mobile numerical application for Down syndrome children using MAIL-SinD as a prototype for mobile numerical application. The prototype was tested to nine DS students from Ipoh Down syndrome Centre (IDSC). This paper propose further enhancement of the prototype due to low mean score of the analysis on the user experience testing. Â© 2014 IEEE.